Microcontroller based power factor corrector - Misran, Noor Hadi (2007)
Now day, power factor is very important in electrical system. Power factor means defined as the ratio of the real power over apparent power. It is a measure of how efficiently electrical power is converted into useful work output. Low power factor is expensive, inefficient and waste power. It is because reduces an electrical system’s distribution capacity by increasing current flow and causing voltage drops. Normally in industry, they have system capacitor bank to improve power factor. But in house we don’t have the system capacitor bank. The project is power factor corrector. This project focuses to need improve power factor for application in home. The objective the project is reducing usage current. In this project, a Microcontroller PIC 16F877A will be used as a brain of the system that will control the system through a PIC Basis programming. The PIC Basic Programming will be developed to control when capacitor can turn on. Input of the Microcontroller is a current transducer. Function of the current transducer to read the current from line. The current transducer can convert 5A to 5 mA. The maximum value can read of current transducer is 5A. We use current transducer because Microcontroller very sensitive device. It only can read voltage from 0V to 5V. When give value greater than 5V to Microcontroller, it can make Microcontroller burnt. When the Microcontroller senses certain current, it will give signal to output to turn on the capacitor. Function of the capacitor to improve level power factor. The benefit improve power factor is reduce of electricity bills, increased electrical system capacity and voltage drop at the point of use will be reduced.